Bentuk Tanggung Jawab Sosial pada UMKM Industri Tahu di Kabupaten Kediri - Sayekti Indah Kusumawardhany (Al-Muraqabah: Journal of Management and Sharia Business, 2022)
The growth of small and medium enterprises (SMEs) also has an impact on the emergence of negative impacts on the surrounding environment. SMEs can use social responsibility as a strategy in maintaining their business continuity. Because SMEs are not only focused on seeking high profits but are more focused on business activities that will continue in the long term, business actors need to maintain good relations with the environment, community, and employees. The type of research used is qualitative. Qualitative research aims to obtain clear and in-depth empirical data from the object of research, so phenomenology is the qualitative research approach. The results of this study indicate that the implementation of social responsibility is motivated by a social spirit, voluntary, and the principle of kinship owned by business owners.